A guidebook to mechanic chemistry - Peter Sykes (Longman, 1986)
The book provides fundamental understanding of organic chemistry: structure, reactivity, and mechanism. New topics inmtroduced include: ipso aromatic substitution; the mechanic bordeline in nucleophilic susbtitution; more use of activation parameters; Dimroth's Et parameter; Hammett's ox and spectroscopic data; and C n.m.r. in biogenesis. etc.